THE LATE KARELIAN IN THE STRATIGRAPHIC SCALE OF RUSSIA: DETERMINATION OF ITS LOWER BOUNDARY AND REGIONAL UNITS IN THE STRATOTYPE AREA - Shul'diner V.I.; Kozyreva I.V.; Levchenkov O.A.; Yakovleva S.Z.; Makeev A.F.; Komarov A.N.; Konopel'ko D.L.; Baltybaev Sh.K. (My University, 2000)
The U-Pb zircon age is determined for stratigraphically important Upper Karelian structures of the northern Ladoga region. The age of the Sortavala Group volcanics is assumed to be 1.97-1.95 Ga that coincides with age of the Outokumpu and Jormua ophiolites in Finland. The Sortavala and coeval Suisar groups are recommended to be distinguish as the Livvian, the initial regional unit of the upper Karelian, which, along with ophiolites of Finland, marks the opening stage of the Svecofennian belt. The overlying Ladoga Group is a stratotype of the early Ladogian marking the mature evolutionary stage of Svecofennides. The upper boundary of the Ladoga Group is established on the basis of gabbroid intrusions intersecting the group and dated back to 1.88-1.89 Ga. The subsequent late Ladogian interval (up to 1.80 Ga) that characterizes an intense volcanism in the region is missing from the successions.